The Effect of Health Education about Menstruation on Psychological Readiness of Pre-Adolescent Girls in Facing Menarche - Widiastini, Luh Putu; Karuniadi, I Gusti Agung Manik (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Adolescence is a period of transition between age and adulthood, where growth spurts occur, secondary sex-features arise, fertility occurs and better psychological and cognitive conditions, in which girls are marked by the emergence of menstruation (menarche). Menarche is the first menstrual period that occurs during puberty in a woman. In some cases, this accelerated growth can affect a woman’s psychological, changes that can occur include or mistakes that often occur. Information that really can be used to improve the ability of young women.Health efforts that can be done to increase knowledge to learn the correct information about menarche for young women, one of which is health promotion through health education. The purpose of this study was to find out the Psychological Impression of Pre-Adolescent Girls (the fifth grade students) Facing Menarche at SDN 02 Sanur, Denpasar.